Antimicrobial Activity Evaluation on Silver Doped Hydroxyapatite/Polydimethylsiloxane Composite Layer. (4th October 2015) - Ciobanu, C. S.; Groza, A.; Iconaru, S. L.; Popa, C. L.; Chapon, P.; Chifiriuc, M. C.; Hristu, R.; Stanciu, G. A.; Negrila, C. C.; Ghita, R. V.; Ganciu, M.; Predoi, D.
Abstract : The goal of this study was the preparation, physicochemical characterization, and microbiological evaluation of novel hydroxyapatite doped with silver/polydimethylsiloxane (Ag:HAp-PDMS) composite layers. In the first stage, the deposition of polydimethylsiloxane (PDMS) polymer layer on commercially pure Si disks has been produced in atmospheric pressure corona discharges. Finally, the new silver doped hydroxyapatite/polydimethylsiloxane composite layer has been obtained by the thermal evaporation technique. The Ag:HAp-PDMS composite layers were characterized by various techniques, such as Scanning Electron Microscopy (SEM), Glow Discharge Optical Emission Spectroscopy (GDOES), and X-ray photoelectron spectroscopy (XPS). The antimicrobial activity of the Ag:HAp-PDMS composite layer was assessed against Candida albicans ATCC 10231 (ATCC—American Type Culture Collection) by culture based and confirmed by SEM and Confocal Laser Scanning Microscopy (CLSM) methods. This is the first study reporting the antimicrobial effect of the Ag:HAp-PDMS composite layer, which proved to be active against Candida albicans biofilm embedded cells.